2000
DOI: 10.1051/rnd:2000107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peri-oestrus progesterone levels and time of ovulation by echography in pigs and influence of the interval between ovulation and artificial insemination (AI) on litter size

Abstract: -Two methods for the determination of ovulation were compared to one ultrasonography performed 5 times a day. Time of ovulation by echography was 40 ± 5.8 h (mean ± SD) after the onset of oestrus. Preovulatory LH rise (two blood samples per day) began near the onset of oestrus but, in our conditions, this parameter could not be used to predict ovulation. The basal level of progesterone (two blood samples per day) was determined with a non-linear model, the timing when progesterone rose more than one SD (0.3 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…The gilts were recorded in oestrus when a female demonstrated all behaviour characteristics ("standing" reaction, active pursuit of the male, etc.) described by Signoret [17] and Terqui et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…The gilts were recorded in oestrus when a female demonstrated all behaviour characteristics ("standing" reaction, active pursuit of the male, etc.) described by Signoret [17] and Terqui et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…The ability of a pig oocyte to be fertilized has been considered to be as short as 8-12 h after ovulation (Hunter 1967a;Hunter and Dziuk 1968). Therefore, insemination after ovulation results in impaired farrowing rate and litter size (Nissen et al 1997;Rozeboom et al 1997;Terqui et al 2000). In addition, in a study on the influence of pre-compared with post-ovulatory insemination (20-15 h and 15-20 h, respectively), on the distribution of spermatozoa in the oviduct, the accessory sperm counts on the zona pellucida and early embryonic development (Kaeoket et al 2002), we found that when sows were inseminated after ovulation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Ces outils ont permis de déterminer le moment d'ovulation. Dans un cadre expérimental, l'échographie est la méthode la plus utilisée mais le dosage de la progestérone peut être utilisé comme alternative à ces méthodes pour dater a posteriori le moment d'ovulation avec une fiabilité équivalente à celle de l'échographie (Terqui et al 2000). Pour connaître avec précision le moment d'ovulation, plusieurs observations (trois et plus) sont indispensables quelle que soit la méthode employée.…”
Section: / Techniques De Détection De L'oestrus Et De L'ovulationunclassified
“…A la dose journalière de 20 mg d'altrenogest et avec 18 j de traitement, environ 95% des femelles ont un oestrus 4 à 7 j après l'arrêt du progestagène. Par ailleurs, l'altrenogest ne permet pas de prédire les ovulations (Terqui et al 2000). Il ne dispense donc pas de détecter les chaleurs.…”
Section: / Maîtrise Pharmacologique De L'oestrus De L'ovulation Et Dunclassified